Soil Chemical attributes under different management systems in Cerrado-Amazon ecotone (Research, Society and Development, 2021)
The Cerrado-Amazonas ecotone occupies 4.85% of the Brazilian territory, with almost 60% of its area deforested. Inadequate soil management practices cause changes in the physical, chemical and biological soil attributes. This study aimed to characterize soil chemistry in different management systems, identifying its efficiency. Ten areas were divided into two soil classes (Ultisol and Entisol               quartzipsamment), each comprising a management system (1 - silvopastoral with 30% shade (SP30), 2 - silvopastoral with 60% shade (SP60), 3 - secondary forest, 4 - native forest, 5 – pasture conventional (CP)). The samples were collected at depths of 0-10, 10-20 and 20-40 cm. The chemical attributes of the soil analyzed were pH, P, K +, Ca2 +, Mg2 +, H + Al3 +, Al3 +, sum of bases (SB), effective cation exchange capacity (CEC), CEC at pH 7, saturation base (V%) and aluminum saturation (m%). The data were submitted to principal component analysis and analysis of variance and Tukey's test (p